Prioritizing the structural and neighborhood preferences of Penang’s condominiums - Abdul Wahab, Siti Maryam; Mokhtar, Ernieza Suhana (Universiti Teknologi MARA Selangor, 2025)
This study examines the preferences of prospective condominium buyers in Penang, Malaysia, with a focus on property structural elements and neighbourhood amenities, as informed by experienced real estate agents. A review of the literature identified twenty key structural features and eighteen important neighbourhood characteristics, including accessibility and community resources. The research involved a purposive sample of 60 real estate professionals, each with at least five years of experience in the local market. These participants assessed the importance of the identified attributes using a self-administered questionnaire. The data analysis generated a relative importance index that ranked the top ten structural and neighbourhood preferences, offering insights into the factors condominium buyers value most. These findings provide valuable guidance for developers, marketers, and policymakers to align their strategies with buyer preferences, ultimately enhancing satisfaction and improving market appeal within Penang’s competitive condominium sector.